THE ROLE OF ORGANIZATIONAL CULTURE IN THE SETIA HATI TERATE BROTHERHOOD (PSHT) IN PROMOTING INDIVIDUAL DISCIPLINE: IMPLICATIONS FOR EMPLOYEE PERFORMANCE - Maspufah, Hayatul; Rakhmawati, Ratih (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study aims to investigate the role of the organizational culture within Persaudaraan Setia Hati Terate (PSHT) in fostering individual discipline and its subsequent implication for employee performance. The research utilizes a qualitative descriptive approach, analyzing data gathered from interviews and observations with members, trainers, and administrators of the organization. The findings indicate that the strong organizational culture of PSHT is highly effective in instilling discipline. Discipline is actively trained through mandatory elements such as timely attendance, strict adherence to training rules, and consistent compliance with the instructor's instructions. This training cultivates essential positive work behaviors, including heightened loyalty, strong sense of responsibility, and better work performance that consistently carry over to members' professional or academic environments. The data shows that members who demonstrate high discipline within PSHT are significantly more regular, diligent, and exhibit better collaborative skills, leading to superior achievement in their employment or studies compared to less disciplined individuals. This research highlights the significant value of non-formal organizational culture as a mechanism for developing human capital. The discipline instilled proves to be a vital factor that contributes positively to overall productivity and serves as a predictor of better professional performance.